High-toughness, high-modulus and high-damping magnesium-based composite material and preparation method thereof

Through the ball mill mixing method and accumulation stacking process, the reinforcement body is uniformly dispersed in the aluminum plate and semi-solid casting is carried out, which solves the problem that existing magnesium-based composite materials are difficult to improve strength, elastic modulus, plasticity and damping performance at the same time, and realizes high strength, high modulus and high damping magnesium-based composite materials.

CN119843125APending Publication Date: 2025-04-18OCEAN UNIV OF CHINA
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202510054812.2
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-01-14
Publication Date
2025-04-18

AI Technical Summary

Technical Problem

Existing magnesium-based composite materials are difficult to improve strength, elastic modulus, plasticity and damping properties simultaneously, resulting in limited applications in the field of lightweighting.

Method used

The reinforcement was prepared by ball mill mixing method, and it was evenly dispersed in the aluminum plate by cumulative stacking and rolling, followed by semi-solid casting to ensure a good interface between the reinforcement and the substrate.

Benefits of technology

The synergistic improvement of high strength, high modulus and high damping performance of magnesium-based composite materials has been achieved, which has significantly improved its application potential in the field of lightweighting.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119843125A_ABST
    Figure CN119843125A_ABST
Patent Text Reader

Abstract

The invention discloses a high-toughness, high-modulus and high-damping magnesium-based composite material and a preparation method thereof, and particularly relates to the field of metal-based composite materials. Comprising the following components in percentage by mass: 1-3.5% of ceramic particles, 0.5-4.5% of carbon nanotubes, 8.5-9.5% of aluminum, 0.5-0.9% of zinc and the balance of magnesium, and the total mass fraction of the components is 100%. Carrying out ball-milling mixing on the carbon nano tube and the ceramic particles to obtain a reinforcement body; dispersing the reinforcements between two aluminum plates, and carrying out accumulative ply rolling to obtain a rolled plate; crushing the rolled plate, mixing the crushed rolled plate with a magnesium ingot and a zinc ingot to obtain a smelting material, smelting the smelting material, stirring when the smelting material is in a semi-solid state, and heating the smelting material to obtain a melt; and casting the melt to obtain the magnesium-based composite material. And the strength, plasticity, elastic modulus and damping performance of the magnesium-based composite material can be improved at the same time.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present application relates to the field of metal-based composite materials, and in particular to a high-strength, high-modulus, high-damping magnesium-based composite material and a preparation method thereof. Background Art

[0002] Due to its advantages of low specific gravity, high specific strength and specific stiffness, good heat dissipation and dimensional stability, and high recycling efficiency, magnesium alloys have shown great application prospects in aerospace, rail transportation, 3C products and other fields. However, performance defects such as low absolute strength, poor room temperature plasticity, and low elastic modulus have hindered the large-scale promotion of magnesium alloys in the field of lightweight. At present, from the perspective of component design, there are two main ways to improve the mechanical properties of magnesium alloys: alloying and preparing composite materials. Due to the low elastic modulus of intermetallic compounds, alloying has limited effect on improving the elastic modulus, and while improving the elastic modulus, it is often accompanied by a decrease in strength, plasticity and damping performance. In contrast, the microstructure and properties of composite materials are designable. In the preparation process, selectively introducing reinforcements (such as ceramic particles and carbon nanotubes) with excellent characteristics such as high modulus, high strength, and high wear resistance into magnesium alloys makes it easier to improve the comprehensive mechanical properties of magnesium alloys. Therefore, selecting suitable reinforcements to prepare magnesium-based composite materials has become an effective way to improve the comprehensive mechanical properties of magnesium alloys.

[0003] At present, there are two ways to introduce reinforcements into magnesium-based composites: external addition method and in-situ method. The in-situ method means that the reinforcement is formed by chemical reaction, which has the advantages of good dispersibility and high interface bonding strength. However, it has great limitations on the types of matrix and reinforcement. For example, the in-situ reaction system found so far is extremely limited. Therefore, the in-situ method greatly reduces the "designability" of magnesium-based composites. The advantage of the external addition method is that the matrix and reinforcement have rich selectivity and designability. However, the external addition method is prone to contamination, air entrainment, and sedimentation in the melt on the surface of the reinforcement, making it difficult to achieve uniform distribution of the reinforcement and good interface bonding with the matrix. As a result, while the strength and elastic modulus of traditional magnesium-based composites are significantly improved, they are often accompanied by a significant decrease in plasticity and damping properties. This performance bottleneck greatly restricts the large-scale application of magnesium-based composites. Summary of the invention

[0004] The main purpose of the present application is to provide a high-strength, high-modulus, high-damping magnesium-based composite material and a preparation method thereof, aiming to solve the problem that existing magnesium-based composite materials cannot simultaneously improve strength, elastic modulus, plasticity and damping performance.

[0005] To achieve the above objectives, the present application provides a high-strength, high-modulus and high-damping magnesium-based composite material. The raw materials of the magnesium-based composite material include the following components in mass fraction: 1-3.5% ceramic particles, 0.5-4.5% carbon nanotubes, 8.5-9.5% aluminum, 0.5-0.9% zinc, and the rest is magnesium. The total mass fraction of the above components is 100%.

[0006] Optionally, the magnesium-based composite material has a yield strength of 124-138 MPa, a tensile strength of 234-252 MPa, an elongation at break of 15.8-17%, a damping value of 0.09-0.094, and an elastic modulus of 62.9-67.5 GPa.

[0007] To achieve the above-mentioned objectives, the present application also provides a method for preparing the above-mentioned high-strength, high-toughness, high-modulus, high-damping magnesium-based composite material, comprising: ball-milling and mixing carbon nanotubes and ceramic particles to obtain a reinforcement; dispersing the reinforcement between two aluminum plates, and performing cumulative rolling to obtain a rolled plate; crushing the rolled plate, and mixing it with a magnesium ingot and a zinc ingot to obtain a smelting material, smelting the smelting material, stirring the smelting material when it is in a semi-solid state, and heating the smelting material to obtain a melt; casting the melt to obtain a magnesium-based composite material.

[0008] Optionally, during the ball milling process, the ball milling speed is 10-80 r / min, and the ball milling time is 2-10 h.

[0009] Optionally, the preparation process of the rolled plate includes: dividing the reinforcement into multiple parts according to mass, and cumulatively laminating two aluminum plates; wherein, in each laminating process, a portion of the reinforcement is dispersed between the two aluminum plates to be laminated, and rolled to obtain a rolled plate.

[0010] Optionally, in each rolling process, the heating temperature is 100-300° C., the holding time is 5-30 min; the rolling temperature is 20-25° C., and the rolling speed is 2-7 m / s.

[0011] Optionally, when the smelting material is in a semi-solid state, the stirring speed is 30-80 r / min, and the stirring time is 1-10 min.

[0012] Optionally, the smelting process includes: heating the smelting material to obtain a semi-solid melt; stirring the semi-solid melt, heating it to a melting temperature, and removing slag; cooling the melt after slag removal to obtain a semi-solid melt; stirring the semi-solid melt, heating it to a melting temperature, and removing slag to obtain a melt.

[0013] Optionally, the melting temperature is 715-725° C., and after the temperature is raised to the melting temperature, melting stirring is performed; wherein the stirring speed is 5-20 r / min, and the stirring time is 1-5 min.

[0014] Optionally, the size of the ceramic particles is 10-60 nm, the diameter of the single-walled carbon nanotubes is 1-10 nm, and the length is 8-30 μm.

[0015] Compared with the prior art, the present invention has the following beneficial effects:

[0016] The preparation method of the high-strength, high-modulus and high-damping magnesium-based composite material of the present invention comprises the following steps: firstly, carbon nanotubes and ceramic particles are ball-milled at a low speed and for a short time to obtain a reinforcement, thereby ensuring the structural integrity of the carbon nanotubes; then, the reinforcement is uniformly dispersed in an aluminum plate by cumulative rolling, and the processing is carried out at room temperature, thereby slowing down the oxidation and oxygen absorption capacity of the reinforcement, and reducing the probability of interface pollution and interface chemical reaction; and the cumulative rolling process is solid-state forming, thereby avoiding air entrainment during the process of adding the reinforcement to the melt, and after multiple cumulative rolling passes, the reinforcement can be tightly embedded in the aluminum plate, thereby suppressing the formation of defects such as holes at the interface, and achieving good interface bonding between the reinforcement and the matrix, thereby simultaneously improving the strength, plasticity, elastic modulus and damping performance of the magnesium-based composite material. BRIEF DESCRIPTION OF THE DRAWINGS

[0017] Figure 1 The present invention relates to a room temperature tensile stress-strain curve of a high-strength, high-modulus and high-damping magnesium-based composite material.

[0018] Figure 2 The tensile strength and elongation at break of the magnesium-based composite material prepared in this application are compared with those of the traditional magnesium-based composite material.

[0019] Figure 3 The elastic modulus and elongation at break of the magnesium-based composite material prepared in this application are compared with those of the traditional magnesium-based composite material.

[0020] The realization of the purpose, functional features and advantages of this application will be further explained in conjunction with embodiments and with reference to the accompanying drawings. DETAILED DESCRIPTION

[0021] In order to make the purpose, technical solutions and advantages of this application clearer, the technical solutions in this application will be clearly and completely described below in conjunction with the drawings in this application. Obviously, the described embodiments are part of the embodiments of this application, not all of them. Based on the embodiments in this application, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of this application.

[0022] The first embodiment of the present invention provides a high-strength, high-modulus and high-damping magnesium-based composite material. The raw materials of the magnesium-based composite material include the following components in terms of mass fraction: 1-3.5% ceramic particles, 0.5-4.5% single-walled carbon nanotubes, 8.5-9.5% aluminum, 0.5-0.9% zinc, and the rest is magnesium. The total mass fraction of the above components is 100%.

[0023] The yield strength of magnesium-based composite materials is 124-138MPa, the tensile strength is 234-252MPa, the elongation at break is 15.8-17%, and the damping value is 0.09-0.094 (strain amplitude is 10 -3 Damping value at 90°), the elastic modulus is 62.9-67.5GPa.

[0024] In this embodiment, the cast magnesium alloy AZ91 is used as the matrix, and nano-ceramic particles and single-walled carbon nanotubes are used as reinforcements. Compared with the traditional ceramic particles (elastic modulus of 73 to 480 GPa) reinforcements, the single-walled carbon nanotubes (CNTs) have a higher elastic modulus (elastic modulus of 0.4 to 4.5 TPa) and also have the ability to improve the damping performance of the AZ91 alloy; in addition, the nano-ceramic particles can simultaneously improve the strength, plasticity and damping performance of the AZ91 alloy, so the magnesium-based composite material of this embodiment can achieve a synergistic improvement in strength, plasticity, elastic modulus and damping performance.

[0025] The second embodiment of the present invention provides a method for preparing a high-strength, high-modulus, high-damping magnesium-based composite material, which specifically comprises the following steps:

[0026] Step S1, ball-milling the carbon nanotubes and the ceramic particles to obtain a reinforcement;

[0027] For example, the size of the ceramic particles is 10-60 nm, the diameter of the single-walled carbon nanotube is 1-10 nm, and the length is 8-30 μm. The ceramic particles include other reinforcements besides TiB2 and AlN particles, such as SiC particles and TiC particles.

[0028] Specifically, the single-walled carbon nanotubes are placed in anhydrous ethanol and subjected to ultrasonic vibration at a power of 180 W for 1 hour to disperse the mutually entangled carbon nanotubes; the ultrasonicated carbon nanotubes are placed in a vacuum drying oven at 50° C. to dry the anhydrous ethanol. After drying, the carbon nanotubes and ceramic particles are placed in a planetary ball mill and mixed at a speed of 10-80 r / min for 2-10 hours, and the mixture is placed in a vacuum drying oven and dried at a vacuum environment of 50° C. for 1 hour to obtain a reinforcement.

[0029] In this embodiment, compared with the traditional dispersion method that relies too much on the ball milling process, that is, high-speed and long-time ball milling is required to achieve uniform distribution of the reinforcement in the matrix, the ball milling process of the present invention has a low speed and a short time, which will not destroy the structure of the carbon nanotubes and maintain their good performance.

[0030] Step S2, dispersing the reinforcement between two aluminum plates, performing cumulative lamination rolling, and obtaining a rolled plate;

[0031] Specifically, the surfaces of the two aluminum plates are polished to a bright finish, requiring that there is no oxide scale and dirt visible to the naked eye on the surface; the reinforcement is divided into multiple portions according to mass, and the two aluminum plates are cumulatively laminated; wherein, in each lamination process, a portion of the reinforcement is dispersed between the two aluminum plates to be laminated, and rolled to obtain a rolled plate.

[0032] It is worth noting that the number of reinforcements can be set according to actual needs. The following takes three portions as an example to specifically explain the preparation process of the rolled plate.

[0033] Step S21, the reinforcement is divided into three parts according to the mass, the first part of the reinforcement is evenly laid between two aluminum plates to obtain a laminated plate, and the laminated plate is placed in a vacuum heat treatment furnace and kept at 100-300° C. for 5-30 minutes; at room temperature, at a speed of 2-7 m / s, the laminated plate is rolled to a thickness of 1 mm in one pass through a double-roll rolling mill to obtain a first rolled plate;

[0034] Step S22, cutting the first rolled plate at a position half the length, grinding the surfaces of the two cut plates with a wire brush to make the surfaces free of visible dirt; evenly laying the second reinforcement between the two plates to obtain a laminated plate, and placing the laminated plate in a vacuum heat treatment furnace, keeping the temperature at 100-300° C. for 5-30 minutes; at room temperature, rolling the laminated plate to a thickness of 1 mm by a double-roll rolling mill at a speed of 2-7 m / s in one pass to obtain a second rolled plate;

[0035] Step S23, repeating step S22 on the second rolled plate to obtain a third rolled plate;

[0036] After the above three rolling passes, the reinforcement has been pre-dispersed into the aluminum plate. In order to improve the dispersion, the third rolled plate is rolled for 3-23 passes, and the rolling process parameters of the cumulative rolling are the same as those of the first three passes.

[0037] In this embodiment, the reinforcement is divided into multiple parts, and during the cumulative rolling process, it is dispersed in batches in the rolled plate to ensure the effect of pre-dispersion during rolling. In the process of directly adding the reinforcement to the molten matrix material or the semi-solid matrix, the surface of the reinforcement will be oxidized due to the high temperature to form oxides (i.e., interface contamination). At the same time, the oxygen adsorbed on the surface of the reinforcement is easy to react chemically with the matrix to form a brittle phase at the interface. In addition, the process of adding the reinforcement to the melt is easy to involve gas, resulting in the formation of holes at the interface. In order to solve the above problems, the present embodiment pre-disperses the reinforcement into the aluminum plate through multiple passes of cumulative rolling. On the one hand, since the rolling temperature is room temperature, the oxidation and oxygen absorption capacity of the reinforcement are greatly slowed down, and the probability of interface contamination and interface chemical reaction is reduced. On the other hand, the cumulative rolling process belongs to a large plastic deformation process and is solid-state forming, which avoids the entrainment of gas during the reinforcement addition process. After multiple passes of cumulative rolling, the reinforcement can be tightly embedded in the aluminum plate, inhibiting the formation of holes at the interface. In addition, an aluminum plate with better rolling formability is selected as the rolling substrate, which is suitable for the composite of more reinforcement particles and the matrix.

[0038] Step S3, crushing the rolled plate, mixing it with magnesium ingots and zinc ingots to obtain a smelting material, smelting the smelting material, stirring the smelting material when it is in a semi-solid state, and heating the smelting material to obtain a melt; further, the smelting material also includes an aluminum ingot to ensure the composition of the matrix. The magnesium ingot is a pure magnesium ingot or a cast magnesium alloy AZ91, and the zinc ingot is a pure zinc ingot.

[0039] The smelting specifically includes: placing the smelting material into a stainless steel crucible, placing the stainless steel crucible into a resistance smelting furnace, smelting the material under the protection of a mixed gas of sulfur hexafluoride and carbon dioxide, heating the smelting material to obtain a semi-solid melt; stirring the semi-solid melt at a stirring speed of 30-80 r / min and a stirring time of 1-10 min; heating the semi-solid melt to 715-725° C. to make it liquid, mechanically stirring the semi-solid melt at a stirring speed of 5-20 r / min and a stirring time of 1-5 min, and stirring the smelting and The oxides formed during the semi-solid stirring process float to the liquid surface and are deslagging; the melt after deslagging is cooled to obtain a semi-solid melt; the semi-solid melt is stirred at a speed of 30-80 r / min and a stirring time of 1-10 min; the temperature is raised to 715-725° C., and the melt is mechanically stirred at a speed of 5-20 r / min and a stirring time of 1-5 min. After the stirring is completed, the melt in the crucible is kept at 715-725° C. for 5-15 min, and the slag is removed to obtain a melt.

[0040] In this embodiment, due to the large viscosity of the semi-solid state, the reinforcement is easier to disperse in the semi-solid state than in the liquid state. Therefore, stirring is performed in the semi-solid state to further improve the dispersion of the reinforcement in the matrix, thereby solving the problem that the reinforcement particles are prone to agglomeration and sedimentation during the external smelting process due to the density difference between the reinforcement and the matrix. The reinforcement is first dispersed into the aluminum plate through an accumulated rolling process of large plastic deformation, and then semi-solid stirring casting is performed. Compared with direct semi-solid stirring casting, the dispersion effect can be improved, thereby increasing the interface bonding ability between the reinforcement and the matrix, and improving the strength, plasticity, elastic modulus and damping performance of the magnesium-based composite material.

[0041] Step S4, casting the melt into a stainless steel mold for casting to obtain a (ceramic particles+CNTs) / AZ91 magnesium-based composite material.

[0042] Example 1

[0043] Step S1, placing 1.5g of single-walled carbon nanotubes in anhydrous ethanol, and performing ultrasonic vibration at a power of 180W for 1h to disperse the mutually entangled carbon nanotubes; placing the ultrasonicated carbon nanotubes in a vacuum drying oven at 50°C to dry the anhydrous ethanol. After drying, the carbon nanotubes and 2g of TiB2 particles are placed in a planetary ball mill, mixed at a speed of 30r / min for 3h, and the mixture is placed in a vacuum drying oven and dried at a vacuum environment of 50°C for 1h to obtain a reinforcement;

[0044] Step S2, polish the surfaces of two aluminum plates with a size of 100×50×1 (mm) to a bright finish, requiring that there is no visible scale and dirt on the surface; divide the reinforcement into three parts according to the mass, evenly lay the first part of the reinforcement between the two aluminum plates to obtain a laminated plate, and place the laminated plate in a vacuum heat treatment furnace and keep it warm at 150°C for 15 minutes; at room temperature, at a speed of 3m / s, roll the laminated plate to a thickness of 1mm through a double-roll rolling mill in one pass to obtain a first rolled plate; cut the first rolled plate at half the length, and brush it with a wire brush. The surfaces of the two cut plates are polished to make them free of visible dirt; the second reinforcement is evenly laid between the two plates to obtain a laminated plate, and the laminated plate is placed in a vacuum heat treatment furnace and kept at 150°C for 15 minutes; at room temperature, the laminated plate is rolled to a thickness of 1 mm by a double-roll rolling mill at a speed of 3m / s to obtain a second rolled plate; the above process is repeated for the second rolled plate to obtain a third rolled plate; the three rolled plates are subjected to 17 passes of cumulative lamination rolling, and the parameters of the rolling process are the same as those mentioned above to obtain a rolled plate;

[0045] Step S3, crushing the rolled plate and mixing it with magnesium ingots and zinc ingots to obtain a smelting material, placing the smelting material in a stainless steel crucible, placing the stainless steel crucible in a resistance smelting furnace, smelting the material under the protection of a mixed gas of sulfur hexafluoride and carbon dioxide, heating the smelting material to obtain a semi-solid melt; stirring the semi-solid melt at a stirring speed of 50 r / min for 5 min; heating the semi-solid melt to 720°C to make it liquid, and mechanically stirring the semi-solid melt at a stirring speed of 10 r / min for 5 min. The melting and semi-solid stirring process is carried out for 3 minutes, and the oxides formed during the smelting and semi-solid stirring process are floated to the liquid surface by stirring, and the slag is removed; the melt after the slag removal is cooled to obtain a semi-solid melt; the semi-solid melt is stirred at a stirring speed of 50r / min and a stirring time of 5min; and the temperature is raised to 720°C, and the melt is mechanically stirred at a stirring speed of 10r / min and a stirring time of 3min. After the stirring is completed, the melt in the crucible is kept at 720°C for 5min, and the slag is removed to obtain a melt;

[0046] Step S4, casting the melt into a stainless steel mold for casting to obtain a (TiB2+CNTs) / AZ91 magnesium-based composite material.

[0047] The magnesium-based composite material obtained in this embodiment was subjected to mechanical property testing to obtain a room temperature tensile stress-strain curve. Figure 1 The room temperature tensile properties, damping and elastic modulus can be obtained, as shown in Table 1:

[0048]

[0049] Example 2

[0050] Step S1, 3g of single-walled carbon nanotubes are placed in anhydrous ethanol, and ultrasonically vibrated for 1h at a power of 180W to disperse the intertwined carbon nanotubes; the ultrasonicated carbon nanotubes are placed in a vacuum drying oven at 50°C to dry the anhydrous ethanol. After drying, the carbon nanotubes and 4g of TiB2 particles are placed in a planetary ball mill, mixed at a speed of 50r / min for 4h, and the mixture is placed in a vacuum drying oven and dried at a vacuum environment of 50°C for 1h to obtain a reinforcement;

[0051] Step S2, polish the surfaces of two aluminum plates with a size of 150×65×1 (mm) to a bright finish, requiring that there is no visible scale and dirt on the surface; divide the reinforcement into three parts according to the mass, evenly lay the first part of the reinforcement between the two aluminum plates to obtain a laminated plate, and place the laminated plate in a vacuum heat treatment furnace and keep it warm at 200°C for 10 minutes; at room temperature, at a speed of 5m / s, roll the laminated plate to a thickness of 1mm through a double-roll rolling mill in one pass to obtain a first rolled plate; cut the first rolled plate at half the length, and brush it with a wire brush. The surfaces of the two cut plates are polished to make them free of visible dirt; the second reinforcement is evenly laid between the two plates to obtain a laminated plate, and the laminated plate is placed in a vacuum heat treatment furnace and kept at 200°C for 10 minutes; at room temperature, the laminated plate is rolled to a thickness of 1 mm by a double-roll rolling mill at a speed of 5 m / s to obtain a second rolled plate; the above process is repeated for the second rolled plate to obtain a third rolled plate; the three rolled plates are subjected to 20 passes of cumulative lamination rolling, and the parameters of the rolling process are the same as those mentioned above to obtain a rolled plate;

[0052] Step S3, crushing the rolled plate and mixing it with magnesium ingots and zinc ingots to obtain a smelting material, placing the smelting material in a stainless steel crucible, placing the stainless steel crucible in a resistance smelting furnace, smelting the material under the protection of a mixed gas of sulfur hexafluoride and carbon dioxide, heating the smelting material to obtain a semi-solid melt; stirring the semi-solid melt at a stirring speed of 60r / min for 5min; and heating the semi-solid melt to 715°C to make it liquid, and mechanically stirring the semi-solid melt at a stirring speed of 5r / min for 5min. The melting and semi-solid stirring process is carried out for 4 minutes, and the oxides formed during the smelting and semi-solid stirring process are floated to the liquid surface by stirring, and the slag is removed; the melt after the slag removal is cooled to obtain a semi-solid melt; the semi-solid melt is stirred at a stirring speed of 60r / min and a stirring time of 5min; and the temperature is raised to 715°C, and the melt is mechanically stirred at a stirring speed of 5r / min and a stirring time of 4min. After the stirring is completed, the melt in the crucible is kept at 720°C for 5min, and the slag is removed to obtain a melt;

[0053] Step S4, casting the melt into a stainless steel mold for casting to obtain a (TiB2+CNTs) / AZ91 magnesium-based composite material.

[0054] The magnesium-based composite material obtained in this example was subjected to mechanical property tests, and the test results of room temperature tensile properties, damping and elastic modulus are shown in Table 2:

[0055]

[0056] Example 3

[0057] Step S1, placing 15g of single-walled carbon nanotubes in anhydrous ethanol, and performing ultrasonic vibration at a power of 180W for 1h to disperse the mutually entangled carbon nanotubes; placing the ultrasonicated carbon nanotubes in a vacuum drying oven at 50°C to dry the anhydrous ethanol. After drying, the carbon nanotubes and 20g of TiB2 particles are placed in a planetary ball mill, mixed at a speed of 70r / min for 6h, and the mixture is placed in a vacuum drying oven and dried at a vacuum environment of 50°C for 1h to obtain a reinforcement;

[0058] Step S2, polish the surfaces of two aluminum plates with a size of 400×150×1 (mm) to a bright finish, requiring that there is no visible scale and dirt on the surface; divide the reinforcement into three parts according to the mass, evenly lay the first part of the reinforcement between the two aluminum plates to obtain a laminated plate, and place the laminated plate in a vacuum heat treatment furnace and keep it warm at 280°C for 15 minutes; at room temperature, at a speed of 5m / s, roll the laminated plate to a thickness of 1mm through a double-roll rolling mill in one pass to obtain a first rolled plate; cut the first rolled plate at half the length, and brush it with a wire brush. The surfaces of the two cut plates are polished to make them free of visible dirt; the second reinforcement is evenly laid between the two plates to obtain a laminated plate, and the laminated plate is placed in a vacuum heat treatment furnace and kept at 280°C for 15 minutes; at room temperature, the laminated plate is rolled to a thickness of 1 mm by a double-roll rolling mill at a speed of 5m / s to obtain a second rolled plate; the above process is repeated for the second rolled plate to obtain a third rolled plate; the three rolled plates are subjected to 21 passes of cumulative lamination rolling, and the parameters of the rolling process are the same as those mentioned above to obtain a rolled plate;

[0059] Step S3, crushing the rolled plate and mixing it with magnesium ingots and zinc ingots to obtain a smelting material, placing the smelting material in a stainless steel crucible, placing the stainless steel crucible in a resistance smelting furnace, smelting the material under the protection of a mixed gas of sulfur hexafluoride and carbon dioxide, heating the smelting material to obtain a semi-solid melt; stirring the semi-solid melt at a stirring speed of 70 r / min for 8 min; heating the semi-solid melt to 720°C to make it liquid, and mechanically stirring the semi-solid melt at a stirring speed of 10 r / min for 8 min. The melting and semi-solid stirring process is carried out for 3 minutes, and the oxides formed during the smelting and semi-solid stirring process are floated to the liquid surface by stirring, and the slag is removed; the melt after the slag removal is cooled to obtain a semi-solid melt; the semi-solid melt is stirred at a stirring speed of 70r / min and a stirring time of 8 minutes; and the temperature is raised to 720°C, and the melt is mechanically stirred at a stirring speed of 10r / min and a stirring time of 3 minutes. After the stirring is completed, the melt in the crucible is kept at 720°C for 5 minutes, and the slag is removed to obtain a melt;

[0060] Step S4, casting the melt into a stainless steel mold for casting to obtain a (TiB2+CNTs) / AZ91 magnesium-based composite material.

[0061] The magnesium-based composite material obtained in this embodiment was subjected to mechanical property tests, and the test results of room temperature tensile properties, damping and elastic modulus are shown in Table 3:

[0062]

[0063] Comparative Example

[0064] A magnesium-based composite material was obtained by adopting the method of "accumulative rolling pre-dispersion + semi-solid casting", with AlN particles and multi-walled carbon nanotubes as reinforcements and AZ91 alloy as the matrix. After testing, its elastic modulus was 55±2GPa and its elongation at break (plasticity) was 22±3%.

[0065] Compared with the magnesium-based composite materials prepared in Examples 1 to 3 of the present application, the magnesium-based composite materials obtained in the comparative example have a lower elastic modulus and do not have high strength, toughness and high damping properties.

[0066] In addition, the performance of the (TiB2+CNTs) / AZ91 magnesium-based composite materials prepared in Examples 1-3 was compared with that of the magnesium-based composite materials prepared by the conventional method. Figure 2 As shown, the composite materials prepared in Examples 1-3 have high tensile strength and their elongation at break is much higher than that of the magnesium-based composite materials prepared by traditional methods. Figure 3 As shown, the elastic modulus and elongation at break of magnesium-based composite materials prepared by traditional methods (including semi-solid casting, semi-solid casting + ultrasonic stirring, ball milling + semi-solid casting, self-propagating high-temperature synthesis, etc.) are usually in an "inverted relationship", that is, the elongation at break will be significantly reduced while the elastic modulus is increased, and vice versa. It can be proved that in this embodiment, the preparation process adopted is "ball milling + cumulative rolling pre-dispersion + semi-solid casting", and the obtained composite material has an excellent combination of elastic modulus and elongation at break.

[0067] The above are only preferred embodiments of the present application, and are not intended to limit the patent scope of the present application. Any equivalent structure or equivalent process transformation made using the contents of the present application specification and drawings, or directly or indirectly applied in other related technical fields, are also included in the patent protection scope of the present application.

Claims

1. A high-strength, high-modulus, high-damping magnesium-based composite material, characterized in that: The raw materials of magnesium-based composite materials include the following components in terms of mass fraction: 1-3.5% ceramic particles, 0.5-4.5% carbon nanotubes, 8.5-9.5% aluminum, 0.5-0.9% zinc, and the rest is magnesium, and the total mass fraction of the above components is 100%.

2. The high-strength, high-modulus, high-damping magnesium-based composite material according to claim 1, characterized in that: The magnesium-based composite material has a yield strength of 124-138 MPa, a tensile strength of 234-252 MPa, a fracture elongation of 15.8-17%, a damping value of 0.09-0.094, and an elastic modulus of 62.9-67.5 GPa.

3. A method for preparing a high-strength, high-modulus, high-damping magnesium-based composite material as claimed in claim 1 or 2, characterized in that: include: The carbon nanotubes and ceramic particles are ball-milled and mixed to obtain a reinforcement; Dispersing the reinforcement between two aluminum plates, and performing cumulative lamination rolling to obtain a rolled plate; The rolled plate is crushed and mixed with a magnesium ingot and a zinc ingot to obtain a smelting material, the smelting material is smelted, the smelting material is stirred when the smelting material is in a semi-solid state, and the smelting material is heated to obtain a melt; The melt is cast to obtain a magnesium-based composite material.

4. The method for preparing the high-toughness, high-modulus and high-damping magnesium-based composite material according to claim 3, characterized in that: During the ball milling process, the ball milling speed is 10-80 r / min, and the ball milling time is 2-10 h.

5. The method for preparing the high-toughness, high-modulus and high-damping magnesium-based composite material according to claim 3, characterized in that: The preparation process of the rolled plate comprises: The reinforcement is divided into multiple parts according to mass, and two aluminum plates are cumulatively rolled; In each lamination process, a portion of the reinforcement is dispersed between two aluminum plates to be laminated, and rolled to obtain a rolled plate.

6. The method for preparing the high-toughness, high-modulus and high-damping magnesium-based composite material according to claim 3, characterized in that: In each rolling process, the heating temperature is 100-300°C, the holding time is 5-30min; the rolling temperature is 20-25°C, and the rolling speed is 2-7m / s.

7. The method for preparing the high-toughness, high-modulus and high-damping magnesium-based composite material according to claim 3, characterized in that: When the smelting material is in a semi-solid state, the stirring speed is 30-80 r / min, and the stirring time is 1-10 min.

8. The method for preparing the high-toughness, high-modulus and high-damping magnesium-based composite material according to claim 3, characterized in that: The smelting process comprises: Heating the smelting material to obtain a semi-solid melt; The semi-solid melt is stirred, heated to a melting temperature, and slag is removed; Cooling the melt after slag removal to obtain a semi-solid melt; The semi-solid melt is stirred, heated to a melting temperature, and slag is removed to obtain a melt.

9. The method for preparing the high-strength, high-modulus and high-damping magnesium-based composite material according to claim 8, characterized in that: The melting temperature is 715-725°C, and after heating to the melting temperature, melting stirring is performed; Among them, the stirring speed is 5-20r / min, and the stirring time is 1-5min.

10. The method for preparing the high-toughness, high-modulus and high-damping magnesium-based composite material according to claim 3, characterized in that: The size of the ceramic particles is 10-60 nm, the diameter of the single-walled carbon nanotubes is 1-10 nm, and the length is 8-30 μm.